Charge density distribution of 3‐(1‐aminoethylidene)‐2‐methoxy‐2‐oxo‐2, 3‐dihydro‐2λ5‐benzo[e][1, 2]oxaphosphinin‐4‐one. Issue 6 (1st December 2013) - Małecka, Magdalena; Mondal, Swastik; van Smaalen, Sander; Paulmann, Carsten
<x xml:space="preserve">Abstract</x> A combined experimental and theoretical study of one oxaphosphinane derivative was made on the basis of a topological analysis of its electron density distributions. The electron density was determined from a high‐resolution X‐ray diffraction data set measured with synchrotron radiation at 100 K, whereas theoretical calculations were performed using density functional theory (DFT) methods at the B3LYP\6‐311++G(3df, 3pd) level of approximation. The charge‐density distribution and analysis of topological properties revealed that the P—O bond is of the transit closed‐shell type. The crystal structure possesses one intra‐ and several intermolecular hydrogen bonds. They were characterized quantitatively by topological properties using Bader's Atoms in Molecules theory. All hydrogen bonds were classified as weak. Further analysis of the experimental electron density by the source function allowed the intramolecular hydrogen bond to be characterized as an isolated hydrogen bond, in contrast to the resonance‐assisted hydrogen bond in related molecules, such as chromone derivatives.